Spice boys: an exploratory study around novel psychoactive substance use on a male acute ward. Issue 3 (21st August 2017) - Place, Charlie; Scally, Andy; Gow, Laura; Wade, Amy; Barrowcliff, Rob; Nasim, Iram; Nyamuchiwa, Miriam
Abstract : Purpose: Novel psychoactive substances (NPS) – often known as "legal highs" – are a varied group of substances that are causing concern due to their possible effects on mental health. Particular concerns have been raised about synthetic cannabinoid receptor agonists often known as "Spice". The purpose of this paper is to identify the prevalence of NPS use and explore any association with acute psychological disturbance. Design/methodology/approach: The authors reviewed the case notes for 153 admissions to a male acute inpatient ward. Prevalence of reported NPS use and admissions to psychiatric intensive care unit (PICU) were recorded. Findings: In total, 18.9 per cent of individuals admitted to acute inpatient care were reported to have used NPS. NPS users were almost ten times as likely as their non-NPS using peers to require care in PICU. This result was statistically significant (Fisher exact test: p <0.001). Although caution is required given the limitations of this study, the data and clinical experience suggest that synthetic cannabinoids may be the specific type of NPS that is being used by this group. Practical implications: Mental health professionals can expect to care for people using NPS in acute inpatient environments, and so they need to understand the nature and effects of these substances. It is possible that NPS use may be associated with sustained acute psychological disturbance. Originality/value: There have been few studies on the prevalence of NPS use in inpatient environments and none of them have published that explore the association with PICU admission. Despite the limitations of this study, it has significant value by identifying an urgent need for comprehensive research in this area.